High responders vs. low responders in cross country running training - Northius, M. E.; Leon, A. S.; Serfass, R. C.; Walker, A. J.; Crow, R. S.; Jacobs, D. R. (Medicine & Science in Sports & Exercise, 1999)
This study attempted to locate variables that differentiate between high-responders (large improvements in race velocity) and low-responders (little to no improvements in race velocity) among Division I collegiate cross country runners (M = 6: F = 10) who participated in identical training programs. Two analytical multivariate models were used: